A mathematical model for university course timetabling problems by considering multi functions. (1st January 2013) - Kaviani, Mohadese; Shirouyehzad, Hadi; Sajadi, Seyed Mojtaba
Timetabling problems are among the most crucial points of the modern world, which is categorised as NP-hard problems. University timetabling problems, particularly the timetables of courses and examinations are among the most difficult tasks that educational institutions are faced with. Manual solution of a university timetabling problem requires a great domain of time and resources. As generating an operable and applicable programme with the least overlapping in the teachers' schedules and overlapping in the curriculum is not easy, various mathematical models and algorithms are proposed to solve such problems. But any of these strategies have considered different limitations due to their operating media and environment. In this paper, we present a mathematical model for university course timetabling. The present study tries to highlight university course time tabling, in which most requirements as well as constraints of an education centre have been examined. The suggested model using a small numeral example was assessed by the software, called 'LINGO 9' whose results indicate that this model is capable of satisfying all limitations along with objectives.